Morphology of melanocytes in hair bulbs and eyes of vitiligo mice. - Boissy, R. E. (1987)
The vitiligo mouse C57BL/6J Ler-vit/vit is a new, murine model for vitiligo in humans. It was studied with respect to morphology and fine structure of melanocytes in hair and eyes before and during depigmentation. The coat of vitiligo mice lightens progressively with age because of an increase in the ratio of white to pigmented hairs with each molt. The bulbs of white hairs are devoid of pigment, and they lack melanocytes. In other respects the epithelium is morphologically normal as determined by light and electron microscopy. The bulbs of pigmented hairs are histologically normal. By electron microscopy, however, some of the melanocytes are shown to have undergone degenerative changes. In addition, disruption of the basement membrane underlying the melanocytes and herniation of melanocytes into dermal papillae were observed at various stages of hair growth. Papillary melanophages are prominent in pigmented as well as in white hair bulbs. Newborn vitiligo mice have no uveal pigment. Pigment appears in the iris and ciliary body by Day 4 and in the choroid by Week 3. On Day 4, along with pigmentation, conspicuous spherical amelanotic cells appear over the anterior border of the iris. These cells become numerous in the ensuing weeks and gradually acquire large melanophagosomes. They occur also in the stroma of the iris and the ciliary body, associated with necrotic melanocytes. The spherical cells are identical to the clump cells of Koganei and are far more numerous in vitiligo mice than in controls. Macroscopically, no progressive decrease in iridial pigment is apparent for the life of the vitiligo mouse. In the choroid, an amelanotic patch surrounds the optic nerve. In the pigmented areas, melanocytes show compartmentalization of melanosomes and degeneration. The retinal pigment epithelium generally appeared continuous. In older animals some epithelial cells contained large fat bodies or were devoid of melanin.